2006
DOI: 10.1016/j.aap.2006.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of freeway traffic parameters leading to lane-change related collisions

Abstract: This study aims at 'predicting' the occurrence of lane-change related freeway crashes using the traffic surveillance data collected from a pair of dual loop detectors. The approach adopted here involves developing classification models using the historical crash data and corresponding information on real-time traffic parameters obtained from loop detectors. The historical crash and loop detector data to calibrate the neural network models (corresponding to crash and non-crash cases to set up a binary classific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(89 citation statements)
references
References 17 publications
(33 reference statements)
0
84
0
Order By: Relevance
“…The VIM for this variable is the weighted average of the reduction in the Gini impurity measure achieved by all splits using variable x j across all internal nodes of the tree, and the weight is the node size. If N is the total number of observations in the training sample, then the formula for the importance for variable x j is given by the following [15]:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The VIM for this variable is the weighted average of the reduction in the Gini impurity measure achieved by all splits using variable x j across all internal nodes of the tree, and the weight is the node size. If N is the total number of observations in the training sample, then the formula for the importance for variable x j is given by the following [15]:…”
Section: Methodsmentioning
confidence: 99%
“…Analyzing 2001 Florida crash database, they found that rear-end crashes are over-presented in the higher speed limits (45-55mph), and the rearend crash propensity is larger for daytime, wet and slippery road surface conditions, male gender, and drivers younger than 21 years of age. Pande and Abdel-Aty [15] in another study employed classification tree based variable selection procedure to identify the important parameters leading to lane-change related freeway crashes, using the traffic surveillance data collected from a pair of dual loop detectors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is a dramatic reduction in the rate of road crash from 1988. Analysts have ascribed this improvement to the activities of the Federal Road Safety Commission in Nigeria since 18 th February 1988. The mandate of the Federal Road Safety Commission is to reduce the rate of traffic crashes to the minimum since at this moment, zero vision has not been contemplated in Nigeria.…”
Section: Analysis Of Road Accident In Nigeriamentioning
confidence: 99%
“…Even though, some studies [14] find that a generalized linear model-based approach may lead to biased estimates when the independent variables demonstrate strong nonlinear features. The commonly used techniques in predicting real-time crash likelihood are Neural Network (NN) [3,15,16] and Support vector machines (SVMs) [17,18].…”
Section: Introductionmentioning
confidence: 99%